PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KOMPETENSI PEDAGOGIK GURU SEKOLAH DASARNEGERI DI KOORDINATOR SATUAN PENDIDIKAN KECAMATAN SEMARANG BARAT - Diah Rini Kuswandari; Ngurah Ayu Nyoman Murniati; Ghufron Abdullah (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2022)
Pedagogic competence must be possessed by all teachers in managing learning in the classroom so that learning objectives can be achieved. The aims of this study were to: 1) determine the magnitude of the influence of academic supervision on teachers' pedagogic competence, 2) determine the magnitude of the influence of organizational culture on teachers' pedagogical competence, and 3) determine the magnitude of the influence of academic supervision and organizational culture together on teachers' pedagogical competence. The research approach used is quantitative. This type of research uses associative research. The population of this study was 471 teachers and the research sample was 216 teachers. Data collection is done by using a questionnaire. The data analysis technique used in this research is descriptive data analysis, prerequisite test which includes normality test, multicollinearity test, heteroscedasticity test, linearity test and hypothesis testing including simple and multiple linear regression. The results showed that: (1) The correlation between academic supervision and teacher pedagogic competence was 0.907. The effect of academic supervision on teacher professionalism is 82.2%, (2) The correlation between organizational culture and teacher pedagogic competence is 0.605. The influence of organizational culture on teachers' pedagogic competence is 66.6%, (3) The correlation between academic supervision and organizational culture on teachers' pedagogic competence is 0.907 and 0.605. The influence of academic supervision and organizational culture on teacher professionalism is 82.2%. The conclusion of this study is that academic supervision and organizational culture affect teacher professionalism by 0.822 or 82.2%. The author suggests that the principal provide direction and guidance, especially regarding the development of students, then the teacher must also pay attention to the talents and interests of students. The principal can reflect and evaluate by increasing the intensity of supervision. Principals can motivate and provide guidance to encourage teachers to complete work well and be oriented towards stability so as to improve teacher performance. Keywords: Pedagogic Competence, Academic Supervision, Organizational Culture.